Induction and activity of glutathione S-transferases extracted from Zonocerus variegatus(Orthoptera: Pyrgomorphidae) exposed to insecticides. (11th November 2014) - Adeyi, A.O.; Akozi, G.O.; Adeleke, M.A.; Agbaogun, B.K.O.; Idowu, A.B.
Abstract : Glutathione S -transferases (GSTs) have been recognized as important metabolic detoxifying enzymes in many phytophagous insects. However, the contribution of GST to insecticide resistance in Zonocerus variegatus (L.) has not been studied. Therefore, we carried out an initial study on the induction and kinetics of GST in Z . variegatus exposed to pyrethroids (PYRs) and Ocimum gratissimum leaf extract. Fifth-instar nymphs of Z . variegatus collected from cassava farms (with no history of insecticide exposure) on the campus of the University of Ibadan were reared to adult stage. Adult insects were divided into four groups of two replicates, each consisting of 30 insects. The groups were exposed to 20 ml of PYR insecticide and 25 mg/dl and 250 mg/dl of O. gratissimum leaf extract, respectively, while the last group served as the control. GST was extracted from the body tissues of the insects using the Bradford method and the kinetics of the enzyme was evaluated using the Lineweaver–Burk plots. No mortality was recorded in insects exposed to 25 mg/dl of O. gratissimum leaf extract, while mortality rates of 93.3 and 43.3% were recorded in insects exposed to PYR insecticide and 250 mg/dl of O. gratissimum leaf extract, respectively. The activity of GST was higher in insects exposed to the insecticides than in the control insects, while a higher enzyme activity was recorded in insects that died after exposure to the insecticides than in insects that were alive after exposure. The GST extracted from insects that were alive after exposure to PYR insecticide and O. gratissimum leaf extract exhibited a high affinity for the glutathione substrate compared with that extracted from insects that died after exposure. Higher GST activity in insects exposed to insecticides is indicative of the role of this enzyme in the metabolic detoxification of insecticides by Z . variegatus .